Coming back home: the reconstruction of the identities of the homecomers (Tempo e Argumento, 2009)
This article aims to discuss the movement of Brazilian emigrants in the beginning of the 21st Century. The return project is part of the migration project: when leaving to “make America”, many men and women stated that their intention was to return to Brazil as soon as they accomplished their migration project, generally translated as to have enough funding to buy a house, a car and to open a business. This paper discusses how men and women live the experience of coming back home, trying to analyze how they reconstruct their way back, and what the effects of the trips on the identitarian configurations in the family and gender relations are. “Homecoming is more difficult than leaving”, say the out goers. Thus we intend to demonstrate that returning is more complex and, in many cases, the emigrants start to live between two places, setting up a transnational identity.
Keywords: transnationalism; return; memory